Manipulating Regular Bearing in 'Golden Delicious'/M9 Apple Trees using GA4+7 and Ethephon. Issue 1 (2nd January 2016) - Atay, Ayşe Nilgün; Koyuncu, Fatma
ABSTRACT: Control of regular cropping in apple is considered critical for fruit growers to ensure their economical sustainability. Irregular flowering can be mitigated by plant growth regulators thanks to their promotion or inhibition effects. In this study, responses of GA4+7 and ethephon on alternate bearing in 'Golden Delicious'/M9 were examined. GA4+7 and ethephon were applied on the same trees during three consecutive years (2010–12). Flowering, yield, shoot growth, and also some fruit quality parameters were assessed. GA4+7 appeared to be more effectual to regulate alternate bearing. The alternate bearing index calculated with yield in successive years was high in control (0.91), moderate in ethephon (0.71), and low in GA4+7 treated trees (0.41). Modified alternate bearing index, based on cluster number, indicated moderate intensity in GA4+7 (0.53) and high intensity in the others. Although GA4+7 reduced crop density at about 50%, there was little variation in yield per tree and crop efficiency due to increasing of fruit size. GA4+7 did not increase shot length after establishment of equilibrium between vegetative and generative growth in 2012. Ethephon slightly reduced vegetative growth and relatively increased fruit size due to the decrease of fruit set.